1949
DOI: 10.1139/cjr49b-048
|View full text |Cite
|
Sign up to set email alerts
|

NITROLYSIS OF HEXAMETHYLENETETRAMINE: II. NITROLYSIS OF l,5-ENDOMETHYLENE-3,7-DINITRO-1,3,5,7-TETRAZA-CYCLOÖCTANE (DPT)

Abstract: When 1,5-enedomethylene-3,7-dinitro-1,3,5,7-tetrazacycloöctane (DPT) is nitrolyzed with nitric acid – ammonium nitrate mixture the products are cyclic trimeric and tetrameric methylenenitramines (RDX and HMX). When the ammonium nitrate in this nitrolysis mixture is replaced by anhydrides such as nitrogen pentoxide or acetic anhydride then terminally esterified linear poly-methylenenitramines such as 1,9-dinitroxy-2,4,6,8-tetranitro-2,4,6,8-tetrazanonane and the 1,9-diacetoxy analogue respectively are obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Considering the importance of NO + judged by some experimental and theoretical results. 5 It was reported that HA could be converted to DPT by AcONO 2 in the presence of HOAc, but hardly reacted to form DPT (1,5-endomethylene-3,7-dinitro-1,3,5,7-tetrazacyclooctane) when only AcONO 2 was used, 6 so the acidic reagents, Ac 2 O and HOAc, are the key factors for the nitrolysis of HA. Other acidic mixing reagents, e.g., HNO 3 -Ac 2 O, HNO 3 -HOAc, and HNO 3 -NH 4 NO 3 -Ac 2 O, are also often used in the nitration or nitrolysis reaction.…”
Section: Nomentioning
confidence: 99%
“…Considering the importance of NO + judged by some experimental and theoretical results. 5 It was reported that HA could be converted to DPT by AcONO 2 in the presence of HOAc, but hardly reacted to form DPT (1,5-endomethylene-3,7-dinitro-1,3,5,7-tetrazacyclooctane) when only AcONO 2 was used, 6 so the acidic reagents, Ac 2 O and HOAc, are the key factors for the nitrolysis of HA. Other acidic mixing reagents, e.g., HNO 3 -Ac 2 O, HNO 3 -HOAc, and HNO 3 -NH 4 NO 3 -Ac 2 O, are also often used in the nitration or nitrolysis reaction.…”
Section: Nomentioning
confidence: 99%
“…DPT, acetic anhydride, ammonium nitrate, and nitric acid 65 [18,39] DPT, hexamine, acetic anhydride, ammonium nitrate, nitric acid, and paraformaldehyde 70 [31] Acetic acid, acetic anhydride, paraformaldehyde, hexamine, nitric acid, and ammonium nitrate 95 [31] TAT, nitric acid and phosphorous pentoxide 80 [ [7] Hexamine, acetic acid, acetic anhydride, boron tri-fluoride, diethyl ether, ammonium nitrate 90 [39] 2…”
Section: Raw Materialsmentioning
confidence: 99%
“…Although DPT is considered as the intermediate of Bachmann process, the smallmolecule route using urea as starting material to prepare HMX via DPT is figured as a promising method for scale-up [6][7][8][9]. The nitrolysis mechanism of DPT has two main disputable opinions in early studies: gradual degradation path and small-molecule recombination path [10][11][12][13].…”
mentioning
confidence: 99%